Determination of costs-race programs and public accounting administration in the university Lisandro Alvarado-UCLA (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
The present research is to determine the cost - racing programs Business Administration and Public Accounting at the University "Lisandro Alvarado " (DAC- UCLA). The scope includes a cost structure, feasible to be extrapolated to other - race programs taught by UCLA, considering the inherent characteristics of each. The establishment of a cost structure will control the expenditures of the budget items to the race and their correspondence to cost objects that, in addition to providing useful information to help find actions that lead to optimization of resources defined. The work was conducted in accordance with principles, standards and generally accepted procedures for the determination of costs, so that the information obtained is relevant and reliable for achieving the goals outlined in the research. This will provide better control of the budgetary resources of UCLA and a solid foundation for the process of decision making. In the research problem objectives, scope and limitations were made. The study was based on a proper conceptual framework of a field, in a logical and sequential approach, where developed and implemented tools and techniques for collecting data validated by experts. The results confirm that the information generated by a given cost structure for UCLA, is sufficient, timely, reliable, accurate and relevant, could even be automated operations made in different Excel tables.
Keywords: cost structure; university budget; decisions